2014
DOI: 10.1016/j.ijid.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for a poor outcome among children admitted with clinically severe pneumonia to a university hospital in Rabat, Morocco

Abstract: The early identification of factors associated with a poor prognosis could improve management strategies and the likelihood of survival of Moroccan children with severe pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
44
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 33 publications
12
44
3
2
Order By: Relevance
“…6 In our study ALRI among infants was 53.5% which in accordance with previous studies by Savitha et al, Broor et al and Sehgal et al where infants with ALRI accounted about 52-62%. 7,8,11 This age group is particularly susceptible due to waning of maternally conferred immunity towards the latter half of infancy.…”
Section: Discussionsupporting
confidence: 93%
“…6 In our study ALRI among infants was 53.5% which in accordance with previous studies by Savitha et al, Broor et al and Sehgal et al where infants with ALRI accounted about 52-62%. 7,8,11 This age group is particularly susceptible due to waning of maternally conferred immunity towards the latter half of infancy.…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of onset of pneumonia, which varies according to authors [ [19], is between 11.7 and 19.7 months. The common denominator concerning age is that it is within 24 months [6] [7] [8].…”
Section: Discussionmentioning
confidence: 99%
“…A child whose mother has no education is 1.5 times more likely to die before the age of 5 than the mother whose education is at least secondary. Jroundi and Demers [19] [23] note no link between socio-demographic characteristics and death.…”
Section: A R Okoko Et Al Open Journal Of Pediatricsmentioning
confidence: 99%
“…Lazzerini et al 34 showed that pneumonia related fatality rates increase in cases with malnutrition. A study by Jroundi et al 33 supported these findings showing that prognosis is worse in children with weight-for-age Z score <1SD. Ahanchian et al 13 pointed out that nutritional support will decrease the recurrence of lower respiratory tract infections in children.…”
Section: Discussionmentioning
confidence: 86%
“…29 Previous studies reported that ETS for Gambian and Alaskan children and smoking of the mother for Finnish children are related with invasive pneumococcal disease. 30---32 Jroundi et al 33 showed that smoking in the house was associated with a worse prognosis in children with pneumonia. As expected, ETS was a significant risk factor for severe pneumonia from our study.…”
Section: Discussionmentioning
confidence: 99%